Trends of CD4 cell count levels at the initiation of antiretroviral therapy over time and factors associated with late initiation of antiretroviral therapy among Asian HIV‐positive patients. Issue 2 (14th March 2014) - Kiertiburanakul, Sasisopin; Boettiger, David; Lee, Man Po; Omar, Sharifah Fs; Tanuma, Junko; Ng, Oon Tek; Durier, Nicolas; Phanuphak, Praphan; Ditangco, Rossana; Chaiwarith, Romanee; Kantipong, Pacharee; Lee, Christopher Kc; et al.
Abstract : Introduction: Although antiretroviral therapy (ART) has been rapidly scaled up in Asia, most HIV‐positive patients in the region still present with late‐stage HIV disease. We aimed to determine trends of pre‐ART CD4 levels over time in Asian HIV‐positive patients and to determine factors associated with late ART initiation. Methods: Data from two regional cohort observational databases were analyzed for trends in median CD4 cell counts at ART initiation and the proportion of late ART initiation (CD4 cell counts <200 cells/mm 3 or prior AIDS diagnosis). Predictors for late ART initiation and mortality were determined. Results: A total of 2737 HIV‐positive ART‐naïve patients from 22 sites in 13 Asian countries and territories were eligible. The overall median (IQR) CD4 cell count at ART initiation was 150 (46–241) cells/mm 3 . Median CD4 cell counts at ART initiation increased over time, from a low point of 115 cells/mm 3 in 2008 to a peak of 302 cells/mm 3 after 2011 ( p for trend 0.002). The proportion of patients with late ART initiation significantly decreased over time from 79.1% before 2007 to 36.3% after 2011 ( p for trend <0.001). Factors associated with late ART initiation were year of ART initiation (e.g. 2010 vs. before 2007; OR 0.40, 95% CI 0.27–0.59; p <0.001), sex (male vs. female; OR 1.51, 95% CI 1.18–1.93; p =0.001) and HIV exposure risk (heterosexual vs. homosexual; OR 1.66, 95% CI 1.24–2.23; p =0.001 and intravenous drug use vs. homosexual; OR 3.03, 95% CI 1.77–5.21; p <0.001). Factors associated with mortality after ART initiation were late ART initiation (HR 2.13, 95% CI 1.19–3.79; p =0.010), sex (male vs. female; HR 2.12, 95% CI 1.31–3.43; p =0.002), age (≥51 vs. ≤30 years; HR 3.91, 95% CI 2.18–7.04; p <0.001) and hepatitis C serostatus (positive vs. negative; HR 2.48, 95% CI 1.−4.36; p =0.035). Conclusions: Median CD4 cell count at ART initiation among Asian patients significantly increases over time but the proportion of patients with late ART initiation is still significant. ART initiation at higher CD4 cell counts remains a challenge. Strategic interventions to increase earlier diagnosis of HIV infection and prompt more rapid linkage to ART must be implemented.